The Challenges of Long Term Ecological Research: A Historical Analysis
XIX, 478 p. 56 illus., 4 illus. in color.
Keywords: This volume explores the challenges of sustaining long-term ecological research through a historical analysis of the Long Term Ecological Research Program created by the U.S. National Science Foundation in 1980. The book examines reasons for the creation of the Program, an overview of its 40-year history, and in-depth historical analysis of selected sites. Themes explored include the broader impact of this program on society, including its relevance to environmental policy and understanding global climate change, the challenge of extending ecosystem ecology into urban environments, and links to creative arts and humanities projects. A major theme is the evolution of a new type of network science, involving comparative studies, innovation in information management, creation of socio-ecological frameworks, development of governance structures, and formation of an International Long Term Ecological Research Network with worldwide reach. The book’s themes will interest historians, philosophers and social scientists interested in ecological and environmental sciences, as well as researchers across many disciplines who are involved in long-term ecological research.